Systematic Literature Review: The Role Of Transfer Pricing Regulations In Reducing Tax - Lestari, Desak Nyoman Lia; Harefa, Tulus; Fuadah, Luk Luk (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
This study aims to examine the role of transfer pricing regulations in reducing tax avoidance practices through a Systematic Literature Review (SLR) approach. The study collects and analyzes 20 scientific articles published between 2018 and 2025, sourced from reputable databases such as Emerald, DOAJ, and ResearchGate. The articles reviewed are publications in either Indonesian or English, fully accessible, and indexed in Scopus, Copernicus, Sinta, or are proceedings from international conferences. The main keyword used in the search process was